2014
DOI: 10.1016/j.diagmicrobio.2013.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of American cutaneous leishmaniasis by enzyme immunoassay using membrane antigens of Leishmania (Viannia) braziliensis

Abstract: This study evaluated the reactivity of membrane antigens of Leishmania (Viannia) braziliensis for the diagnosis of ACL by enzyme immunoassay (EIA). Promastigotes of L. (V.) braziliensis were grown in medium 199 and lysed in a sonicator. Sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) and Western blotting showed that specific proteins of L. (V.) braziliensis (apparent molecular weights 36 kDa and 48-56 kDa) were recognized by sera from ACL patients. These proteins were eluted from the SDS-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Indirect Immunofluorescence Assay (IFA), Enzyme Linked Immunosorbent Assay (ELISA), Enzyme Immune Assay (EIA), Flow Cytometry and Immunoblotting (Western blot) are the current methods available for serological diagnosis of CL [64]. Some studies have shown Western blot as the most sensitive (100%) [65].…”
Section: Serology and Direct Antigen Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indirect Immunofluorescence Assay (IFA), Enzyme Linked Immunosorbent Assay (ELISA), Enzyme Immune Assay (EIA), Flow Cytometry and Immunoblotting (Western blot) are the current methods available for serological diagnosis of CL [64]. Some studies have shown Western blot as the most sensitive (100%) [65].…”
Section: Serology and Direct Antigen Detectionmentioning
confidence: 99%
“…Some studies have shown Western blot as the most sensitive (100%) [65]. EIAs have a reported sensitivity of 93.3% and a specificity of 90.8% [64].However, these tests are expensive, require laboratory infra-structure and are time consuming. Flow cytometry has been shown to be more sensitive than ELISA but less specific [66].…”
Section: Serology and Direct Antigen Detectionmentioning
confidence: 99%
“…The opposite occurs with tests that aim to visualise the parasite, which present high specificity and low sensitivity. Molecular diagnoses have also been used, although their utilisation is limited by the need for specialised centres to perform the technique, as well as by their high cost [8][9][10]. Figure 1 describes the clinical path of this review.…”
Section: Introductionmentioning
confidence: 99%